In-situ neutron diffraction of a quasicrystal-containing Mg alloy interpreted using a new polycrystal plasticity model of hardening due to 10.2 tensile twinning. (January 2018) - Agnew, S.R.; Singh, A.; Calhoun, C.A.; Mulay, R.P.; Bhattacharyya, J.J.; Somekawa, H.; Mukai, T.; Clausen, B.; Wu, P.D.
Abstract: Due to the excellent balance of strength and ductility exhibited by some Mg-Zn-RE (Y subgroup rare earth element) alloys, which contain icosahedral quasicrystalline precipitates, it is of interest to examine their deformation mechanisms. The internal strain evolution Mg-3at%Zn-0.5 at%Y with 4 vol% i-phase was measured using in-situ neutron diffraction. The extruded samples exhibit an initially weak <10.0> || extrusion direction "rod texture, " distinct from the normally strong texture of extruded Mg alloys, but the grain size is unexceptional (16.7 ± 2.1 μm). The initially weak texture contributes to a nearly symmetric yielding response between tension and compression. The hardening responses are asymmetric, however, since 10.2 extension twinning is significantly more active during compressive straining, despite the initially weak texture. In-situ neutron diffraction tension and compression experiments parallel to the extrusion direction, together with elasto-plastic self-consistent (EPSC) crystal plasticity modeling, reveal the strength and hardening behavior of individual slip and twinning modes. The previously published twinning-detwinning (TDT) model is implemented within the EPSC framework, and it is proven effective for describing the observed, mild tension-compression asymmetry. This is not possible with previous EPSC-based models of twinning. Finally, the description of hardening within the TDT model is modified, in order to accurately describe the evolution of internal strains within the twins. Highlights: Quasicrystal containing Mg alloy is examined using in-situ diffraction for the first time. Quasicrystals are ineffective as strengtheners, due to low volume fraction and number density. Quasicrystals effective for grain refinement, which can yield high strength and ductility. A simple model of twin hardening is introduced, which is easy to parameterize. The model describes yield asymmetry and twin fraction and internal strain evolution.